23-5n=-7(n-3)-4

Simple and best practice solution for 23-5n=-7(n-3)-4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 23-5n=-7(n-3)-4 equation:


Simplifying
23 + -5n = -7(n + -3) + -4

Reorder the terms:
23 + -5n = -7(-3 + n) + -4
23 + -5n = (-3 * -7 + n * -7) + -4
23 + -5n = (21 + -7n) + -4

Reorder the terms:
23 + -5n = 21 + -4 + -7n

Combine like terms: 21 + -4 = 17
23 + -5n = 17 + -7n

Solving
23 + -5n = 17 + -7n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '7n' to each side of the equation.
23 + -5n + 7n = 17 + -7n + 7n

Combine like terms: -5n + 7n = 2n
23 + 2n = 17 + -7n + 7n

Combine like terms: -7n + 7n = 0
23 + 2n = 17 + 0
23 + 2n = 17

Add '-23' to each side of the equation.
23 + -23 + 2n = 17 + -23

Combine like terms: 23 + -23 = 0
0 + 2n = 17 + -23
2n = 17 + -23

Combine like terms: 17 + -23 = -6
2n = -6

Divide each side by '2'.
n = -3

Simplifying
n = -3

See similar equations:

| 0.1x+0.2y=-0.2 | | Log^4*16=2 | | 7x-(5x+4)=9x-25 | | 25=2u+3u | | 2(x+4)4=0 | | 7.4x-13.4=31 | | 8u-u=21 | | 128-4y+2y=100 | | (c-3)(2c)=2c(c-3)-c^2+4 | | 16x-14=-110 | | 18x+14=13x+4 | | 5x+40=15-50 | | x+11=7x+65 | | 3a-3+2a=200-3a+2a | | (2b-4)=7b+2 | | 5=4x(1+x) | | 7.35x+66.15=132.3 | | -x+1=28+2x | | 3-4x+8x-5x=3x+12-15x+7 | | 4x-8.6=48.1-5x | | 8+12+(-9)-(-6)= | | 4x-7=29-2x | | 56-7x=-48+6x | | 5(x+1)=6-2(5x-7) | | x^2+9x-12=6+2x | | 8n+3=9 | | 18=13x+4x | | 0.6(w-12)=0.2w | | -8b-[5b(7b-9b)]-[-3+(20b+3)]=0 | | 2x-2=-11.6-2x | | 11x-1=5.3+2x | | 8x-2+6x=5x+4-7x |

Equations solver categories